If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (300 + -20q) * q + -20q + -2400 = 0 Reorder the terms for easier multiplication: q(300 + -20q) + -20q + -2400 = 0 (300 * q + -20q * q) + -20q + -2400 = 0 (300q + -20q2) + -20q + -2400 = 0 Reorder the terms: -2400 + 300q + -20q + -20q2 = 0 Combine like terms: 300q + -20q = 280q -2400 + 280q + -20q2 = 0 Solving -2400 + 280q + -20q2 = 0 Solving for variable 'q'. Factor out the Greatest Common Factor (GCF), '20'. 20(-120 + 14q + -1q2) = 0 Ignore the factor 20.Subproblem 1
Set the factor '(-120 + 14q + -1q2)' equal to zero and attempt to solve: Simplifying -120 + 14q + -1q2 = 0 Solving -120 + 14q + -1q2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. 120 + -14q + q2 = 0 Move the constant term to the right: Add '-120' to each side of the equation. 120 + -14q + -120 + q2 = 0 + -120 Reorder the terms: 120 + -120 + -14q + q2 = 0 + -120 Combine like terms: 120 + -120 = 0 0 + -14q + q2 = 0 + -120 -14q + q2 = 0 + -120 Combine like terms: 0 + -120 = -120 -14q + q2 = -120 The q term is -14q. Take half its coefficient (-7). Square it (49) and add it to both sides. Add '49' to each side of the equation. -14q + 49 + q2 = -120 + 49 Reorder the terms: 49 + -14q + q2 = -120 + 49 Combine like terms: -120 + 49 = -71 49 + -14q + q2 = -71 Factor a perfect square on the left side: (q + -7)(q + -7) = -71 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| (300-2q)-20q-2400=0 | | 2x^3+2x^2+8x=0 | | 9x^2-49x+4=0 | | 6t+8=33+t | | 3x+4y-6y^2+90=0 | | 35x^4-28x^7=0 | | 3x+3=x+13 | | 4x=2x+40 | | x+18=24 | | 600=30d | | 2x-3[4-(3x-7)]= | | 10-11d=-5d-4 | | 5n+4=n+24 | | 9z/7=-30 | | 5(x+9)=x+69 | | 9x^2+24x+16= | | d^2+10d-684.5217391=0 | | 8=-4b+6b | | -16x^2-8x+24=0 | | -300-(-4x)=-8x | | -21x^2-21x+42=0 | | -16t^2+32t+20=0 | | 3x-y-7=0 | | 6x=2x+14 | | 5x^2-13x-28=0 | | 8x+15=4x-5 | | y=-0.5x^2+4.5x | | 78x^4+143x^3-39x^2-26=0 | | 0=20a^2-4a | | 18x^2-39x+15=0 | | 3n-1=11 | | 6x^2+19+3=0 |